The Influence of Online Service Quality, Sales Promotion, and Perception of Easy on the Decision to Use OVO E-Wallet in National University FEB Students - Rizka Angelina Octaviola; Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the impact of advances in electronic payments and value insights on the decision to use the Ovo E-Wallet for FEB National University students. The data of this study used primary data in the form of a questionnaire. The population of this study were FEB students at the National University who used the Ovo E-Wallet. The research sampling method used was purposive with a total of 86 respondents. Research results The results of this study indicate that online service quality, sales promotion, perceived convenience have a positive and significant influence on the decision to use OVO E-Wallet. The value of the coefficient of determination (Adjusted R Square) is 0.524%, this indicates that the variables of online service quality, sales promotion and perceived convenience have an influence on the decision variable on the use of OVO E-Wallet for FEB National University students by 0.541 or 54.1% while the rest 45.9% is explained by other variables not examined in this study.